If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -4) + 4(x + -8) + (x + -3) = 2x + -1 Reorder the terms: 8(-4 + x) + 4(x + -8) + (x + -3) = 2x + -1 (-4 * 8 + x * 8) + 4(x + -8) + (x + -3) = 2x + -1 (-32 + 8x) + 4(x + -8) + (x + -3) = 2x + -1 Reorder the terms: -32 + 8x + 4(-8 + x) + (x + -3) = 2x + -1 -32 + 8x + (-8 * 4 + x * 4) + (x + -3) = 2x + -1 -32 + 8x + (-32 + 4x) + (x + -3) = 2x + -1 Reorder the terms: -32 + 8x + -32 + 4x + (-3 + x) = 2x + -1 Remove parenthesis around (-3 + x) -32 + 8x + -32 + 4x + -3 + x = 2x + -1 Reorder the terms: -32 + -32 + -3 + 8x + 4x + x = 2x + -1 Combine like terms: -32 + -32 = -64 -64 + -3 + 8x + 4x + x = 2x + -1 Combine like terms: -64 + -3 = -67 -67 + 8x + 4x + x = 2x + -1 Combine like terms: 8x + 4x = 12x -67 + 12x + x = 2x + -1 Combine like terms: 12x + x = 13x -67 + 13x = 2x + -1 Reorder the terms: -67 + 13x = -1 + 2x Solving -67 + 13x = -1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -67 + 13x + -2x = -1 + 2x + -2x Combine like terms: 13x + -2x = 11x -67 + 11x = -1 + 2x + -2x Combine like terms: 2x + -2x = 0 -67 + 11x = -1 + 0 -67 + 11x = -1 Add '67' to each side of the equation. -67 + 67 + 11x = -1 + 67 Combine like terms: -67 + 67 = 0 0 + 11x = -1 + 67 11x = -1 + 67 Combine like terms: -1 + 67 = 66 11x = 66 Divide each side by '11'. x = 6 Simplifying x = 6
| 66+6y-20=16y-10-2y | | Z^3+5z+3z^2+1+4-2z^2= | | 24/25=s/35 | | -10/9i | | 4(n+6)=8-4(n-2) | | 12+p=8+7 | | =x^2+4x | | 2(cos(2pi))=0 | | 4m^5n^0(5m^3)= | | 2/7x234/1 | | 4(2x+-1)=.5(16x+-8) | | ln(3x-2)=2.3 | | 3xwhat=123 | | 12y+10y=20y-3 | | 3(n+8)=3-3(n-7) | | 12+9y=9 | | 17-5x=35 | | 3xa=123 | | 12y+10y=20y-60 | | 1/4x=17 | | 7(n+8)=2-5(n-6) | | 8x+1y=26 | | =3x^2-9x | | -15+31=-2(x+1) | | 2(5h)+25=40h | | -16z-0.7=-26z+2.1 | | 81a^2=4 | | 0=x^2-9x^4 | | 2ln(y)=y | | 5(3+8)=(X*3)+(X*8) | | 8r+9r=-21 | | (2x-8)-10=2-8x |